Synthesis, Characterization, Biological Activity and DNA Binding Studies of Metal Complexes with 4-Aminoantipyrine Schiff Base Ligand - B. Anupama; M. Padmaja; C. Gyana Kumari (E-Journal of Chemistry)
A new series of transition metal complexes of Cu(II),Ni(II),Co(II), Zn(II) and VO(IV) have been synthesized from the Schiff base ligand (L) derived from 4-amino antipyrine and 5- bromo salicylaldehyde. The structural features of Schiff base and metal complexes were determined from their elemental analyses, thermogravimetric studies, magneticsusceptibility, molar conductivity, ESI-Mass, IR, UV-VIS, 1H NMR and ESR spectral studies. The data show that the complexes have composition of ML2 type. The UV-VIS, magnetic susceptibility and ESR spectral data suggest an octahedral geometry around the central metal ion. Biological screening of the complexes reveals that the Schiff base transition metal complexes show significant activity against microorganisms. Binding of Co(II) complex with calf thymus DNA (CT DNA) was studied by spectral methods.